Evaluation of Light Fluence Distribution Using an IR Navigation System for HPPH‐mediated Pleural Photodynamic Therapy (pPDT). (22nd October 2019) - Zhu, Timothy C.; Ong, Yihong; Kim, Michele M.; Liang, Xing; Finlay, Jarod C.; Dimofte, Andreea; Simone, Charles B.; Friedberg, Joseph S.; Busch, Theresa M.; Glatstein, Eli; Cengel, Keith A.
Abstract: Uniform light fluence distribution for patients undergoing photodynamic therapy (PDT) is critical to ensure predictable PDT outcomes. However, current practice when delivering intrapleural PDT uses a point source to deliver light that is monitored by seven isotropic detectors placed within the pleural cavity to assess its uniformity. We have developed a real‐time infrared (IR) tracking camera to follow the movement of the light point source and the surface contour of the treatment area. The calculated light fluence rates were matched with isotropic detectors using a two‐correction factor method and an empirical model that includes both direct and scattered light components. Our clinical trial demonstrated that we can successfully implement the IR navigation system in 75% (15/20) of the patients. Data were successfully analyzed in 80% (12/15) patients because detector locations were not available for three patients. We conclude that it is feasible to use an IR camera‐based system to track the motion of the light source during PDT and demonstrate its use to quantify the uniformity of light distribution, which deviated by a standard deviation of 18% from the prescribed light dose. The navigation system will fail when insufficient percentage of light source positions is obtained (<30%) during PDT. Abstract : Uniform light fluence distribution for patients undergoing photodynamic therapy (PDT) is critical to ensure predictable PDT outcomes. We have developed a real‐time infrared (IR) tracking camera to follow the movement of the light point source and to determine the surface contour of the treatment area. We conclude that it is feasible to use an IR camera‐based system to track the motion of the light source during PDT and demonstrate its use to quantify the uniformity of light distribution, which deviated by a standard deviation of 18% from the prescribed light dose.